Exploring Pre-Service Teachers’ Satisfaction in a Virtual International Internship Program in Thailand - Ardiyansah Yuli Tri; Batubara Widiyanita Riska; Auliya Khilyatul Prativi (Journal of Teaching and Education, 2025)
In recent years, the rapid advancement of digital technology has encouraged many educational institutions to transform their teaching and learning processes into online learning. At the University of Muhammadiyah Gresik (UMG), one of the focuses of this transformation is teaching practice. UMG provides students with an opportunity to enhance their teaching skills by joining the International Internship Program in Thailand. The essence of the program is to give students experiences as Pre-Service Teachers in teaching English to elementary school students. However, due to the shift to online learning, the program was conducted virtually. Despite this adjustment, preservice teachers found it challenging to carry out their teaching practice effectively. This research focused on analyzing pre-service teachers’ satisfaction toward the online learning process. The researchers distributed a survey to 11 (eleven) pre-service teachers enrolled in the international internship program. Five indicators were used in the survey: (1) instructor-to-student interaction, (2) affordances, (3) institutional support, (4) student-to-student interaction, and (5) course design and technical development. Based on the results, it was found that the institution provided full support to the pre-service teachers, which led to their satisfaction with the assistance. However, in general, the pre-service teachers were not satisfied with the overall online learning process. The main problems occurred in the areas of interaction, affordances, course design, and technical development.